Hypertension Diagnosis and Management: New findings from the recent guidelines - Parisa Ghasemiyeh; Soliman Mohammadi-Samani (Shiraz University of Medical Sciences, 2024)
Hypertension is a common disorder around the world which is mainly asymptomatic and in this regard, it is known as a silent killer disease. Hypertension can induce various complications including cardiovascular disorders i.e. heart failure, angina, and acute coronary syndrome, renal failure, cerebrovascular disease, and retinopathies, in this regard, regular screening, early diagnosis and management of hypertension is crucial. In general, angiotensin converting enzyme inhibitors (ACEIs), angiotensin receptor blockers (ARBs), calcium channel blockers (CCBs), β-blockers, and thiazide diuretics are considered as first-line agents for hypertension management. However, selection of a suitable antihypertensive regimen is mainly affected by the patients' specific conditions and also their comorbidities. In this review, the latest versions of different hypertension guidelines including "2023 European Society of Heart (ESH) Guidelines for the Management of Arterial Hypertension", "2020 International Society of Hypertension Global Hypertension Practice Guidelines" and "2017 ACC/ AHA/ AAPA/ ABC/ ACPM/ AGS/ APhA/ ASH/ ASPC/ NMA/ PCNA Guideline for the Prevention, Detection, Evaluation, and Management of High Blood Pressure in Adults" and also recently related publications have been reviewed. Moreover, pharmacotherapy in special groups of patients and those with comorbidities have been summarized according to the latest guidelines that are currently available for each predisposing disease. Finally, hypertension crises diagnosis and management are discussed.